2016
DOI: 10.7314/apjcp.2016.17.3.1535
|View full text |Cite
|
Sign up to set email alerts
|

Adult Primary Myelodysplastic Syndrome: Experience from a Tertiary Care Center in Pakistan

Abstract: Background: Primary myelodysplastic syndrome (MDS) is an acquired clonal disorder of myeloid progenitor cells, characterized by peripheral cytopenias in the presence of hypercellular marrow with dysplastic features. Our aim was to study the demographical and clinicopathological features of adult Pakistani patients with MDS at disease presentation. Materials and Methods: This single centre study was conducted at Liaquat National Hospital and Medical College, extending from January 2010 to December 2014. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
9
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 16 publications
9
9
3
Order By: Relevance
“…The most common presenting complaint in our patients was loss of appetite followed by weakness. In our study mean Hb was 7.7 g/dl which is in concordance with a previous national study [1] and higher as compared to other studies done in Pakistan, China and India [2,6,8] and lower as compared to Turkey, Greece and Poland [9,10,15]. In our study, mean platelet count was 82 ×10 9 /l, which is in concordance with a national study and also seen in India [1,8].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The most common presenting complaint in our patients was loss of appetite followed by weakness. In our study mean Hb was 7.7 g/dl which is in concordance with a previous national study [1] and higher as compared to other studies done in Pakistan, China and India [2,6,8] and lower as compared to Turkey, Greece and Poland [9,10,15]. In our study, mean platelet count was 82 ×10 9 /l, which is in concordance with a national study and also seen in India [1,8].…”
Section: Discussionsupporting
confidence: 82%
“…MDS is generally considered a preleukemic disorder and is prevalent in elder individuals in western world [5]. However, median age at diagnosis in our study was younger which concurs with other studies done in Asia [1][2][3][4][6][7][8] as compared to the studies from west with higher median age in MDS (Greece, Germany, Poland) [10,14,15]. In our study we observed male predominance which is universally seen in this disorder [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations